2014
DOI: 10.5114/kitp.2014.45672
|View full text |Cite
|
Sign up to set email alerts
|

CARDIAC SURGERY Validation of EuroSCORE II risk model for coronary artery bypass surgery in high-risk patients

Abstract: IntroductionDetermining operative mortality risk is mandatory for adult cardiac surgery. Patients should be informed about the operative risk before surgery. There are some risk scoring systems that compare and standardize the results of the operations. These scoring systems needed to be updated recently, which resulted in the development of EuroSCORE II. In this study, we aimed to validate EuroSCORE II by comparing it with the original EuroSCORE risk scoring system in a group of high-risk octogenarian patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Only a few series offer results comparable to ours, such as that of Stavridis et al (2.23) or that of Kar et al (1.94) for any type of cardiac surgery included, or that of Laurent et al for aortic valve replacement or that of Kalender et al (6.77) for emergency coronary surgery or that of De Oliveira et al and that of Taamallah et al for surgery of infectious endocarditis.…”
Section: Discussionsupporting
confidence: 63%
“…Only a few series offer results comparable to ours, such as that of Stavridis et al (2.23) or that of Kar et al (1.94) for any type of cardiac surgery included, or that of Laurent et al for aortic valve replacement or that of Kalender et al (6.77) for emergency coronary surgery or that of De Oliveira et al and that of Taamallah et al for surgery of infectious endocarditis.…”
Section: Discussionsupporting
confidence: 63%
“…The risk score calculations available for this study are calculated based on EuroSCORE I and not the updated EuroSCORE II, why there is a risk of misclassification of high‐risk patients due to use of the outdated model; however, EuroSCORE I has been found to overestimate 45 and EuroSCORE II to underestimate mortality 4,46,47 . It is, therefore, reasonable to assume that the potential improvement of the model is not attributable to the choice of EuroSCORE model.…”
Section: Discussionmentioning
confidence: 99%
“…However, we 45 and EuroSCORE II to underestimate mortality. 4,46,47 It is, therefore, reasonable to assume that the potential improvement of the model is not attributable to the choice of EuroSCORE model.…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…In their patient population, for the very high risk patients (observed mortality 11%), EuroSCORE II predicted mortality was 6.5% (significant underestimation). Kalender et al 19 reported octagenarians (105 patients) who underwent isolated coronary artery surgery, but the old additive EuroSCORE was used for risk group categorisation. The discriminative power of Euro-SCORE II model was not shown for risk group categories in any of aforementioned papers.…”
Section: Discussionmentioning
confidence: 99%